DIFFERENCE MODULO LABELING - Rekha, S.; Maheswari, V. (Journal of physics. Conference series, 2019)
In this paper, We prove that cycle Cn is a difference modulo labeled graph. We investigate the graph Pn2 and C3(t) is a difference modulo labeling. Here, the formulated edge labeling is considered as plaintext and with the help of affine cipher, we investigate a method of encryption and decryption of a message for the system of secured communication.